Behavioural Response of Oreochromis niloticus Fingerlings Exposed to Sub-Lethal Concentrations of Imidacloprid - Asuquo, Philomena E.; Eteng, Sunday U.; Ifon, Honor T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Imidacloprid, a neonicotinoid pesticide that was once thought to be a solution to environmental pollution caused by previous pesticides like organophosphates and organochlorines has raised global concern recently. The present study aimed at assessing the effect of Imidacloprid on the behaviour of a commercially important fish species, Oreochromis niloticus. The study involved a 48 h sub-lethal toxicity test which was carried out with 0, 5, 10, 20, and 40 ppm of Imidacloprid. Fingerlings of O. niloticus weighing between 18 and 32g were exposed to these concentrations in a static bioassay with continuous aeration. Regular observation of the clinical signs revealed that fish exposed to higher concentrations of Imidacloprid displayed behavioural abnormalities such as erratic behaviour, respiratory stress, and irregular nervousness. The findings of this study revealed that Imidacloprid is toxic and causes behavioural distress on O. niloticus fingerlings. Therefore, there is urgent need for further studies to determine safe limit of Imidacloprid and other pesticides in the environment. Unregulated disposal of toxic pesticides should be avoided, to ensure human safety and environmental sustainability.